Social Capital, Biocultural Heritage, and Commoning for Inclusive Sustainability of Peasant Agriculture: Three Case Studies in Argentina, Bolivia, and Chile; [Capital Social, Patrimônio Biocultural E Bens Comuns Para a Sustentabilidade Inclusiva Da Agricultura Camponesa: Três Estudos de Caso Na Argentina, Bolívia E Chile] - Saez-Tonacca, L (Universidade Federal do Parana, 2023)
Social issues and theoretical background: the sustainability of human societies depends on the intergenerational transmission of capital stocks, whether natural, social or economic. With ever more competition for economic resources, sustainability must increasingly focus on the mutual reinforcement of social and natural capitals. This perspective is particularly relevant for peasant agriculture and producers, who are constantly at risk of social and economic exclusion, but whose social and natural capitals remain important, though often underutilized, even by the peasants themselves. The concepts of commoning and social capital are useful for addressing these issues and activating biocultural heritage from an ethically inclusive sustainability perspective. Objective and methods: We seek to understand how peasants organize to collectively achieve goals of social and economic inclusion that could promote their sustainability and resilience in the face of economic constraints. Using field surveys and participatory action research, we analyzed the social, economic, and environmental factors that fostered the emergence and sustainability of producer organizations and their value chains. This was done in three peasant organizations in Argentina, Bolivia and Chile, whose common starting point is the valorization of traditional quinoa grain, but which differ greatly in terms of size, internal dynamics and organizational trajectories. Results: The successes and challenges of the social innovations implemented in the three cases studied provide lessons on how farmers can mobilize their social capital and leverage the resources of their cultural and natural capitals to achieve ethically inclusive sustainability. While some lessons remain context-specific, others appear to be independent of the size and place of organizations, and several demonstrate the importance of socio-ethical interactions cultivated both within organizations and with consumers. © 2023 Universidade Federal do Parana. All rights reserved.